2019
DOI: 10.1002/lary.27925
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Analysis of Surgical Approaches to Bilateral Vocal Fold Immobility

Abstract: Objectives Bilateral vocal fold immobility (BVFI) is a rare and life‐threatening condition in which both vocal folds are fixed, resulting in airway obstruction associated with life‐threatening respiratory compromise. Treatment of BVFI is largely surgical and remains an unsatisfactory compromise between voice, breathing, and swallowing. No comparisons between currently employed techniques currently exist. We sought to employ computational fluid dynamics (CFD) modeling to delineate the optimal surgical approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In Rios study, PCE allowed for a greater increase in the glottal area, as well as reduced airflow velocity and resistance; and the postoperatively achieved triangular shape (isosceles triangle) of the glottis may contribute to a more homogeneous distribution of airflow in the anterior-posterior axis, as pointed out by the authors. Further improvement of airflow resistance after additional glottic expansion was also observed in a BVFP patient with baseline glottal area of 50.4 mm 2 [ 5 ]. In our study, we took into account both pre- and postoperative measurements.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In Rios study, PCE allowed for a greater increase in the glottal area, as well as reduced airflow velocity and resistance; and the postoperatively achieved triangular shape (isosceles triangle) of the glottis may contribute to a more homogeneous distribution of airflow in the anterior-posterior axis, as pointed out by the authors. Further improvement of airflow resistance after additional glottic expansion was also observed in a BVFP patient with baseline glottal area of 50.4 mm 2 [ 5 ]. In our study, we took into account both pre- and postoperative measurements.…”
Section: Discussionmentioning
confidence: 91%
“…This is also a limitation of our study as all models assumed rigid airway walls. Rios et al [ 5 ] suggested a nonlinear relationship between the cross-sectional area and airflow velocity and resistance, as well as that there probably are “alteration points,” at which airflow parameters favorably increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The respiratory air ow can be in a laminar, transitional, or turbulent state, and turbulence simulations were performed on the subject model using the Reynolds-averaged Navier-Stokes (RANS) equation and the k-ω turbulence equation [7,14].…”
Section: Cfd Proceduresmentioning
confidence: 99%
“…With the continuous advances in high-resolution imaging, and uid mechanics, computational uid dynamics (CFD) has been promoted for air ow studies in the airways, allowing for the visualization of air ow in the airways through distinctive pictures and the calculation of local ow variables such as volume ow, velocity, pressure, wall shear stress, and vortex motion [4]. CFD is often applied in the study of airway diseases, such as nasal diseases and obstructive sleep apnea hypoventilation syndrome [5,6], vocal cord dysfunction [4,7], and laryngotracheal stenosis [8]. Airway dynamics in infants and children have been less studied, and some studies have used unrealistic symmetric anatomical models to predict air ow dynamics [9,10], while a few reports have reconstructed realistic three-dimensional (3D) anatomical models of the airway from high-resolution computed tomography (CT) or magnetic resonance imaging (MRI) data for hydrodynamic studies of subglottic stenosis and tracheomalacia in pediatric patients [11][12][13].…”
Section: Introductionmentioning
confidence: 99%